Pemberdayaan IRT Geblek di Kelurahan Trimurjo melalui Digitalisasi dan Peningkatan Kualitas Produk untuk Kemandirian Ekonomi dan Ketahanan Pangan Lokal - Dani Anggoro; Karnila Ali; Ardiansyah Japlani (JURPIKAT, 2025)
Geblek Mbak Sun Home Industry (IRT) in Trimurjo Village processes cassava into geblek, a traditional Yogyakarta delicacy popular in Lampung. This enterprise employs 20 workers with an average daily production of 200 kg of cassava. However, it faces several challenges, including limited product shelf life, lack of flavor innovation, simple financial recording, absence of standardized operating procedures (SOP), limited access to clean water, and restricted marketing reach. The Community Service Program (PkM) was implemented through observation, socialization, product and packaging innovation training, financial and SOP training, digital marketing training, technology adoption, and mentoring. The results showed improvements in product shelf life through vacuum sealer technology, development of two new product flavors, adoption of digital financial recording, establishment of production SOPs, digital marketing through WhatsApp Business, Marketplace, and website platforms, as well as market expansion with increased sales beyond the Trimurjo area